Computational design and experimental substantiation of conformationally constrained peptides from the complex interfaces of transcriptional enhanced associate domains with their cofactors in gastric cancer. (October 2021) - Zhang, Donglei; Wu, Hongna; Zhao, Jing
Abstract: Transcriptional enhanced associate domains (Teads) are the downstream effectors of the hippo signaling pathway and have been recognized as attractive druggable targets of gastric cancer. The biological function of Teads is regulated by diverse cofactors. In this study, the intermolecular interactions of Teads with their cognate cofactors were systematically characterized at structural, thermodynamic and dynamic levels. The Teads possess a double-stranded helical hairpin that is surrounded by three independent structural elements β-sheet, α-helix and Ω-loop of cofactor proteins and plays a central role in recognition and association with cofactors. A number of functional peptides were split from the hairpin region at Tead–cofactor complex interfaces, which, however, cannot maintain in native conformation without the support of protein context and would therefore incur a considerable entropy penalty upon competitively rebinding to the interfaces. Here, we further used disulfide and hydrocarbon bridges to cyclize and staple the hairpin and helical peptides, respectively. The chemical modification strategies were demonstrated to effectively constrain peptide conformation into active state and to largely reduce peptide flexibility in free state, thus considerably improving their affinity. Since the cyclization and stapling only minimize the indirect entropy cost but do not influence the direct enthalpy effect upon peptide binding, the designed conformationally constrained peptides can retain in their native selectivity over different cofactors. This is particularly interesting because it means that the cyclized/stapled, affinity-improved peptides can specifically compete with their parent Teads for the cofactor arrays as they share consistent target specificity. Graphical Abstract: ga1 Highlights: Intermolecular interactions of Teads with their cofactors are systematically characterized. Peptides deriving from Tead–cofactor interface exhibit large disorder without context support. Cyclization and stapling are used to constrain peptides into native conformation. Cyclization and stapling only improve peptide affinity but do not change peptide specificity.